Komunikasi Bisnis Investor Relations PT Mayora Indah Tbk Sebagai Upaya Mewujudkan Harapan Investor dan Mengembangkan Kerjasama Bisnis Perusahaan - , Marshelia Gloria Narida, Prof. Nunung Prajarto, M.A ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The main purpose of Go public is to increase the amount of the company capital and the positive impact tothe credibility and reputation of the company. However, in its development Go public has been make significant impact for the growing of the business aspects, and also thesharing of responsibility in a company. The relation between company and investor not just in capital and compliance to the law that is mandatory for the public company. Annual report, and financial analysis are not become a main benchmark anymore for the investor in doing stock investment. Communication between company, and investor have become the strength of the company in fulfill the investor expectation and development of the business aspect that comes from selling stock to the public. Based on this analysis, therefore the purpose of this research is to get a picture of the implementation of business communication that is done by the company to fulfill the investor expectation, and also the development of the company business aspect, one of them is in the cooperation of the company business. The aim in establishing the special division is to manage the way company in doing communication to the investor, and it is also become the real example how important the way company communicates to the investor that must be done by the company itself. This research examines from the program arrangement, implementation of the program, evaluation of the program, up to the problem analysis and technical stock analysis that is done by special division. The aim of the special division itself is to manage the relationship between company and investor. The company that is examined from this study is PT Mayora Indah Tbk, operates in package food and beverage industry that was go public since 1990. Thesis title: business communication of the investor relation PT Mayora Indah Tbk in order to realizing the investor expectation, and the development of the cooperation of business communication. The diversity of the investor interests, investor character, and also the problems that is influence investor decision in investment and business cooperation, have become a challenge for the special division that is handle investor relation in running its function and role as a communication development and also company liason between company and investor. Fast and up to date information service, are the key success factors which are unarguable in realizing the investor expectation that will impact to the company profit.